2018
DOI: 10.31289/simbollika.v4i1.1465
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Deiksis Waktu Pada Tuturan Dosen yang Berlatar Belakang Budaya Berbeda

Abstract: AbstrakTuturan dosen FKIP Universitas Samudra yang mengandung deiksis sering salah ditafsirkan oleh mahasiswa. Kesalahtafsiran tersebut berkaitan dengan pemahaman makna tuturan/ujaran dengan acuannya. Salah satu faktor penyebab kesalahtafsiran itu adalah latar belakang budaya yang berbeda sehingga mempengaruhi bentuk-bentuk bahasa yang digunakan. Hal ini mengakibatkan komunikasi tidak berjalan sesuai dengan yang diharapkan. Berdasarkan hal tersebut, permasalahan dalam penelitian ini adalah mengetahui bagaimana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Chaer dalam (Effendi et al, 2018) memiliki pandangan dieksis. Baginya dalam penuturan dieksis akan selalu memiliki rujukan yang tidak tetap pada kata yang digunakan.…”
Section: Pendahuluanunclassified
“…Chaer dalam (Effendi et al, 2018) memiliki pandangan dieksis. Baginya dalam penuturan dieksis akan selalu memiliki rujukan yang tidak tetap pada kata yang digunakan.…”
Section: Pendahuluanunclassified
“…The study on time deixis has been carried out by [25] has similarities, discussing time deixis. The result of the study both found time deixis of present, continuous, and past.…”
Section: Time Deixismentioning
confidence: 99%
“…Deixis expressions are essential to creating effective communication The function of deixis is to unite language in a context (Nurleli & Rahmawati, 2020). Deixis is a word that refers to something that depends on the context of the speaker's speech (Effendi et al, 2018). Deixis makes easier for people to interact and communicate both orally and in writing (Purwandari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mawarsih (2014) stated "The internet resource most widely used by users is electronic mail". E-mail is communication where the sender of the message and the recipient of the message as the perpetrator of communication are not in the same place (Effendi et al, 2018). Email acts as a digital medium for connecting individuals and transmitting messages from one person to another (Stevani, 2014).…”
Section: Introductionmentioning
confidence: 99%